Seabuckthorn (Hippophae rhamnoides L.) in trans-Himalayan Ladakh, India - Stobdan, Tsering; Dolkar, Phuntsog; Chaurasia, O.P.; Kumar, Bhuvnesh (Defence Life Science Journal, 2017)
Seabuckthorn (SBT) is an ecologically and economically important plant species of trans-Himalayan Ladakh. Once considered a thorny menace, SBT is now looked upon as a means for sustainable development of the trans-Himalayan region. Several antioxidant rich SBT-based products are being developed and commercialized. SBT berry collection from natural habitat has become an important activity in the region since the year 2001. Currently, the demand for SBT exceeds the supply capacity of the region. Cultivation of SBT on 2500 ha would result in annual net income of Rs 491 crore. Anticipating the high demand for SBT, studies are underway to meet the long term goal to introduce plantation of SBT on vast barren land. Potential of the lesser-known shrub has been recognized by several R&D organizations. In recent years a number of research institutes in India are working on the lesser known shrub. This article summarizes the advancement of research on SBT of trans-Himalayan Ladakh origin.